2018
DOI: 10.1186/s10020-018-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of menstrual effluent: diagnostic potential for endometriosis

Abstract: BackgroundEndometriosis is a chronic and underdiagnosed disease which affects 5–10% of women of childbearing age and is characterized by growth of endometrial tissue outside of the uterus, most often in the peritoneal cavity. Delay in diagnosis is a major problem for management of this disorder, and treatment is often not initiated until the disease has progressed for many years. Although the exact etiology of endometriosis remains unknown, retrograde menstruation is recognized as a common underlying factor le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
102
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 52 publications
14
102
0
1
Order By: Relevance
“…Antibody-based therapy has seen a major revolution as polyspecific monoclonal antibodies are capable of targeting multiple tumor antigens with specificity without affecting normal bystander cells [ 106 ]. More than 60 antibody–drug conjugates are currently undergoing clinical trials [ 107 ], and 6 antibody–drug conjugates have received FDA approval for cancer therapy [ 108 ].…”
Section: Conjugate Delivery Systemsmentioning
confidence: 99%
“…Antibody-based therapy has seen a major revolution as polyspecific monoclonal antibodies are capable of targeting multiple tumor antigens with specificity without affecting normal bystander cells [ 106 ]. More than 60 antibody–drug conjugates are currently undergoing clinical trials [ 107 ], and 6 antibody–drug conjugates have received FDA approval for cancer therapy [ 108 ].…”
Section: Conjugate Delivery Systemsmentioning
confidence: 99%
“…If unresolved, the negative effects of dysbiosis can be acute and/or long lasting [ 2 , 3 ]. Dysbiosis is linked to the pathogenesis of common neonatal conditions including necrotizing enterocolitis (NEC) and sepsis [ 4 ] as well as the development of autoimmune diseases later in life [ 2 , 3 ]. Human milk has been linked to improved infant outcomes with respect to acute and long-term disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…There are described different types of human endometrial stem cells (HESCs): epithelial-with confirmed location in the basalis of endometrial epithelium, as was postulated [72] stromal/mesenchymal, endothelial, side population-which can differentiate into epithelial and stromal endometrial cells [81], a niche for human epithelial stem cells, and label-retaining cells (LRCs) [82]. All these stem cells can be actually identified with specific markers for immunohistochemistry in endometrial biopsy and/or can be isolated from menstrual blood, being available some devices, as menstrual cups for collection [83]. After repeated examinations of endometrium specimens in all phases of the menstrual cycle, it was concluded that endometrial regenerative cells are located in the basalis, the functionalis being shed at every menstruation, and the basalis which remains intact is the origin of each new cycling endometrium [73].…”
Section: Endometrial Stem/regenerative/progenitor Cells As the Originmentioning
confidence: 88%